A new class of MPV type reduction in group 4 alkoxide complexes of salicylaldiminato ligands: Efficient catalysts for the ROP of lactides, epoxides and polymerization of ethylene. (15th January 2015) - Chakraborty, Debashis; Mandal, Dipa; Ramkumar, Venkatachalam; Subramanian, V.; Vijaya Sundar, J.
Abstract: New titanium (IV), zirconium (IV) and hafnium (IV) alkoxide complexes supported by the tridentate [O, N, N] salicylaldiminato ligands were synthesized in high yields and characterized by conventional spectroscopic techniques and single crystal X-ray analysis. The structural composition for some of these complexes was as a result of in situ intramolecular Meerwein–Ponndorf–Verley (MPV) type reduction of the imine moiety from the ligand, resulting in the formation of unexpected amido compounds. Theoretical calculations were performed at the DFT level to calculate the energy barrier for this reduction and rationalize the reactivity pattern. These complexes were found to be active towards the bulk ring opening polymerization (ROP) of rac -lactide ( rac -LA), l -lactide (l -LA) and ε -caprolactone (CL), resulting in polymers with good number average molecular weight ( M n ) and controlled molecular weight distributions (MWDs). The poly(lactic acid) (PLA) resulting from rac -LA were predominately heterotactic. Interestingly, these compounds were found to catalyze the ROP of epoxides such as rac -cyclohexene oxide ( rac -CHO), rac -styrene oxide ( rac -SO) and rac -propylene oxide ( rac -PO) under solvent free condition. The kinetic and mechanistic studies associated with the polymerization have been included. In addition, these compounds were found to be useful as precatalysts for the polymerization of ethylene. Graphical abstract: Highlights: Group 4 complexes containing [O, N, N] salicylaldiminato ligands is described. Intramolecular MPV type reduction results in the formation of unexpected amido compounds. These complexes were found to be active towards the bulk ROP. These compounds were found to be useful as precatalysts for the polymerization of ethylene.